Adapted Physical Exercise as Therapy in Managing Obesity among Persons with Down Syndrome - Adeleke, Owoade Philip; Ogabor, Joseph Odey; Orim, Samuel Orim; Apie, Martina Ayibeya; Ewa, James Abua; Osaji, Nsagha Nkang; Igbineweka, Paul Osa; Olayi, James Eburikuri; Ahueansebhor, Emmanuel; Orim, Matthew Ashike; Sanda, Francis Ademola; Ama-Abasi, Racheal Daniel; et al. (International Journal of Child Health and Nutrition, 2025)
This study investigated the efficacy of adapted physical exercise in managing obesity among persons with Down Syndrome (ID) in selected special schools in Cross River state. Three null hypotheses were generated for the study. A quasi-experimental research design was adopted. Two special schools and 20 persons with DS were purposively selected from the Special Schools Centre, Ibom Layout, and the Special Education Centre, Ikom, both in Cross River State, Nigeria. The age distribution of the participants is between 6-16 years. Adapted physical activities were used as a therapeutic intervention for six weeks. Kilograms Assessment Scale (KAS) (0.76) was used as an instrument for data collection. ANCOVA was used for data analysis. Results indicated that persons with ID who received intervention (adapted physical exercise) had their body weight reduced. Age and sex did not affect the efficacy of the intervention. It was recommended that physical exercise should be adopted in the management of obesity among persons with DS.